Function of metals and supports on the hydrodeoxygenation of phenolic compounds - Deepa, Ayillath K.; Dhepe, Paresh L. (ChemPlusChem, 2014)
Hydrodeoxygenation (HDO) is an important process for removing oxygen from lignin-derived phenolic monomers to obtain chemicals that can be used as fuel or fuel additives. A systematic study is performed to check the effects of supports (acidic, neutral, basic) and noble metals (Pd, Pt, Ru) on the HDO of phenol, guaiacol, and eugenol. Evaluation of the combinations of metals and supports under the similar reaction conditions shows that the metals supported on a highly acidic support (SiO2-Al2O3) yield complete hydrogenation products with the possibility of C[BOND]O bond cleavage to achieve a real HDO activity, whereas on a mildly acidic support (gamma-Al2O3), a complicated product distribution is achieved, and neutral (C) and basic (HT) supports give restricted hydrogenation activity but yield the products with very high selectivity. On the basis of the results, reaction pathways are suggested and deliberated. The catalysts show reproducible activity in recycle runs. The catalysts are characterized by various techniques (XRD, TEM, TPD, ICP-OES) to establish the catalyst activityproperty relationship.

ffects of cations, anions and H+ concentration of acidic ionic liquids on the valorization of polysaccharides into furfural - Matsagar, Babasaheb M.; Dhepe, Paresh L. (New Journal of Chemistry, 2017)
The valorization of hemicellulose into valuable chemicals, such as C5 sugars and furfural, in a one-pot fashion is crucial. In this work, acidic ionic liquids in the presence of water showed high yields of C5 sugars (>80%) with >99% conversion of hemicelluloses at 160 degrees C. With a water + toluene biphasic solvent system, within 4 h, an 85% furfural yield was obtained directly from hemicellulose in a one-pot fashion using a catalytic amount of 1-methyl-3-(3-sulfopropyl)-imidazolium hydrogen sulfate. It was seen that Bronsted acidic ionic liquids (BAILs) perform better than solid acid [Faujasite and Mordenite zeolites; ion exchange resin, Amberlyst-15] and mineral catalysts [HCl and H2SO4]. The higher activity of BAILs compared to solid acids and mineral acids was correlated to the Hammett acidity function (Ho) and ion-dipole type of interactions. The catalysts were characterized using NMR (H-1 and C-13), elemental analysis and TGA to confirm that they were stable under reaction conditions and were thus recyclable.

Formic-acid-induced using recyclable-ionic liquids as catalysts for lignin conversion into aromatic co-products - Singh, Sandip K.; Dhepe, Paresh L. (Waste and Biomass Valorization, 2019)
Lignin has been widely named as a sustainable and renewable bioresource of energy, fuels, chemicals and materials, particularly phenolic chemicals production on Earth. These bio-derived compounds are in great potential need of biorefinery to valorize complete plant biomass. Lignin depolymerization showed a great promise approach to convert into low molecular aromatic products. In this report, high molecular weight (54,000 Da) lignin depolymerization into maximum yields (87%), (>= 95 +/- 6% mass balance) using a formic acid along with dual (-SO3H) functionalized imidazole-based recyclable (4 times) Bronsted acidic ionic liquids (BAILs) as catalysts have been investigated in H2O-CH3OH (1:5, v/v) at 120 degrees C for 1 h. The structural correlations between the lignin and aromatic products were studied by bulk (CHNS, GPC, etc.) and molecular (UV-Vis, FT-IR, NMR (1D/2D) levels experimental techniques. Additionally, the identification of aromatic products was carried out by applying HPLC, GC and GC-MS techniques. Graphic Addition of a formic acid into Bronsted acidic ionic liquids improved the catalytic efficiency significantly for lignin depolymerization into 87% low molecular weight aromatic products. [GRAPHICS] .
Keywords: Bulk and molecular levels analysis; depolymerization; Dual functionalized ionic liquids; Formic acid; lignin